The requirement and maintenance programme of roadside landscape at Shah Alam City Center / Nurida Sabarina Zahari - Zahari, Nurida Sabarina (Universiti Teknologi MARA, 2005)
Landscape, although is a new subject in Malaysia, even it was an important role into modem development is very clearly when the more of human is being neglect about the role and functions of the roadside landscape in our today’s living. Nowadays, issues of pollution has obvious has brought us to thinking about the environmental balancing that becomes out of date. Therefore, such of alternatives has been taking into these landscaping to making it more attractive. This reality is has get attention from local authority see that landscape can repairs the environmental condition to gives comfortable, healthy, harmonies and safety. Landscaping is a very complex subject. It is practical, yet aesthetically demanding. An art, it requires the many and varied skills of craftsmen for implementation. Good landscaping should be beautiful, of course but on the practical side of the ledger, landscaping should also serve many functions. In fact, every part of a well conceived landscape functions. From such practical achievements some are as a protector from direct sun, temperature control, as a barrier zone to noise, smoke, and air pollution. In addition also to blocking winds, and sheltering from rain while controlling the drainage of surface water to merely providing colors and fragrances to be sensed with enjoyment, well-designed landscaping handles many problems. Landscaping should not be considered an expense but rather a capital improvement to increase property values significantly. An investment should always provide an excellent return if properly designed, implemented, and maintained. From an environmental standpoint, it results in saving on utility bills. Spaces made useful, comfortable, relaxing and stimulating contribute much to enjoyable living.